La polyphonie argumentative dans le discours de presse - Moussa Mousli (Multilinguales)
Journalistic writing employs and mobilizes a number of discursive devices, such as polyphony and argumentation. These two processes combine in certain cases to form a whole discursive process peculiar to itself which is referred to as "argumentative polyphony". The objective of this article is to reflect on and problematize the notion of “argumentative polyphony” in the journalistic chronicles of Sid Ahmed SEMIANE and Hakim LAALAM. Through this study, we aim to understand the function of argumentative polyphony and its use in the press (the period after the word use should be removed) speech via a linguistic study inspired by the theories of argumentation by Oswald Ducrot (1980/1984)) and Jean-Claude Anscombre.